Sequências Didáticas em Espiral como Material Alternativo de Apoio, em Situações de Ensino, à Educação de Jovens e Adultos - Jerônimo, Thiago Henrique (Universidade Federal de Catalão, 2022)
We present in this academic production an alternative approach to science classes in the 9th grade of elementary school in the Youth and Adult Education modality, E.J.A, whose main objective is to think about our actions based on the pedagogy of the American psychologist Jerome Seymour Bruner (1915 -2016). The classes were taught in order to prepare them for the physics content that they will cover in high school, validating the spiral curriculum method, and using the discovery learning method too, making the students' learning more active. Bruner defended that it was possible to teach any content to students of any age, as long as it was done honestly, and so through these studies and using expository and dialogic classes, we can soften the impact that students suffer when they advance to high school and if encounter never-before-seen and complex content, such as mechanics and electromagnetism. However, the application as planned did not follow the pre-established directions, the application of the educational product took place remotely and partially due to the COVID-19 pandemic, and required a series of adaptations, such as the use of Digital Information and Communication Technologies. – TDIC, and schedule changes.
Didactic Sequences in Spiral as Alternative Support Material, in Educational Situations, for Youth and Adult Education
Keywords: Aprendizagem ativa de Física; Bruner; E.J.A.; 1.05.00.00-6 Física